2018
DOI: 10.1021/acsomega.8b00933
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ligand Straining in Complexation of Eu3+–Am3+ Ions by TPEN and PPDEN, Scalar Relativistic DFT Exploration in Conjunction with COSMO-RS

Abstract: To search for new ligands suitable for the separation of minor actinides (MA) from lanthanides (Ln) in nuclear waste reprocessing, theoretical (density functional theory) studies were carried out on the complexation (structures, bonding, and thermodynamics) of La 3+ , Sm 3+ , Eu 3+ , and Am 3+ complexes with moderately soft donor ligands TPEN [ N , N , N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…10a, and a depiction of selected valence MOs are shown in Figure 10b. We focused on analysis of the valence orbitals rather than the electronic excitations, because, as shown in previous studies, 87,88 such analysis is sufficient to qualitatively elucidate coordination properties.…”
Section: Iiid Electronic Structure Of Eu 3+ -Ligand Complexesmentioning
confidence: 99%
“…10a, and a depiction of selected valence MOs are shown in Figure 10b. We focused on analysis of the valence orbitals rather than the electronic excitations, because, as shown in previous studies, 87,88 such analysis is sufficient to qualitatively elucidate coordination properties.…”
Section: Iiid Electronic Structure Of Eu 3+ -Ligand Complexesmentioning
confidence: 99%
“…The MO diagrams for valence orbitals of [Eu 3+ -NA×(H2O)3] 3+ and [Eu 3+ -NA×(H2O)4] 3+ appear in Figure 10a, and a depiction of selected valence MOs are shown in Figure 10b. We focused on analysis of the valence orbitals rather than the electronic excitations, because, as shown in previous studies, 87,88 such analysis is sufficient to qualitatively elucidate coordination properties.…”
Section: Iiid Electronic Structure Of Eu 3+ -Ligand Complexesmentioning
confidence: 99%
“…38 The bulk of the computational work does not report the Gibbs free energy, nor SFs, but instead focuses on comparisons of minimized structures to experimentally determined geometries, 14−20,24,26,27,40−42,45−47 or analysis of molecular orbital composition and electron density. 17,19,20,23,26−28,44−46 Relatively few papers report ΔG 298 K values, 13,25,29,30,32,43,44 and those that do, typically report stability constants for complexes on only a single metal for comparison with experiment. 25,30,43,44 For example, Wang et al calculated a SF of 5000 compared to their experimentally determined value of 60, which corresponds to an error in ΔG(298) of less than 3 kcal/mol, at the B3LYP/ECP(28/ 60)MWB-SEG/6-31G(d) level.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17,19,20,23,26−28,44−46 Relatively few papers report ΔG 298 K values, 13,25,29,30,32,43,44 and those that do, typically report stability constants for complexes on only a single metal for comparison with experiment. 25,30,43,44 For example, Wang et al calculated a SF of 5000 compared to their experimentally determined value of 60, which corresponds to an error in ΔG(298) of less than 3 kcal/mol, at the B3LYP/ECP(28/ 60)MWB-SEG/6-31G(d) level. 32 Trumm et al reported SF calculations on BTP and several close analogues ranging from 7 to 80 for the separation of Cm 3+ /Eu 3+ at the B3LYP/ ECP(28/60)MWB-SEG/aug-cc-pVTZ level.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation